Roles of leadership styles and relationship-based employee governance in open service innovation - Ahmed, Farooq; Naqshbandi, M. Muzamil; Kaur, Sharan; Ng, Boon Kwee (Emerald, 2018)
Purpose: The purpose of this paper is to investigate the relationship of leadership styles (paternalistic, authentic and democratic) with relationship-based employee governance and open service innovation. Design/methodology/approach: Data were collected using a structured questionnaire from 422 medical professionals working in the Malaysian healthcare sector. Findings: Results of several statistical analyses showed that the three leadership styles positively influence relationship-based employee governance and open service innovation. Results also confirmed the mediating role of relationship-based employee governance in the relationships between the three leadership styles and open service innovation. Research limitations/implications: This research used a cross-sectional study design; use of a longitudinal research design in future research can provide a better interpretation of the underlying causality. A policy insight can be drawn from this research to generate awareness about effective leadership styles and the role of relationship-based employee governance in the successful implementation of open service innovation in the Malaysian healthcare sector. Originality/value: This paper contributes to leadership, open innovation, and organizational governance literature by highlighting how leadership styles affect relationship-based employee governance and open innovation. It also offers policy insights to practitioners in the Malaysian healthcare sector on how to enhance open service innovation outcomes.